Attitude Toward Abortion in University Students - Huamani Cahua, Julio César (2017)
In this study we explored the attitude towards abortion in 400 students of four universities in the city of Arequipa (100 students per university). The instrument used was the Garcia Abortion Attitude Scale (1990). It was found that the average of 67,833 points indicates a favorable attitude toward abortion. Likewise, no differences were found regarding age, gender or university of origin; However, there were significant differences (p <0.05) according to career. Likewise, the variables investigated did not explain the attitude towards abortion (p> 0.1293; R2= 0.0434).